Motor learning and performance from principles to application - Schmidt, Richard A. (Richard Allen) 1941-2015; Lee, Timothy Donald 1955- (Human Kinetics, 2020)
Motor Learning and Performance, Sixth Edition, constructs a conceptual model of factors that influence motor performance, outlines how motor skills are acquired and retained with practice, and shows how to apply those concepts to a variety of real-world settings